Pengaruh Kepribadian Ekstrover dan Introver Terhadap Keterampilan Berbicara Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Muhammadiyah Makassar (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to determine the effect of extroverted and introverted personalities on speaking skills. This type of research is a quantitative research with a survey method (expo facto), with a comparative causal design. The objects in this study were students of the Indonesian language and literature education study program. The total population is 238 students, the sample size is 15%, namely 36 students. Accidental sampling technique. The results showed that there were 55.6% or 20 students with introverted personalities and 44.4% or 16 students with extroverted personalities. The results of the mean scores of students' speaking skills show that students with introverted personalities have better speaking skills scores than students who have extroverted personalities. The mean score of students with introverted personalities is 15.65 while the average score of students with extroverted personalities is 13.25. From the results of hypothesis testing with a one-way ANOVA test, the value of Fcount is 1.655, Ftable 4.13, a significance level of 0.05, so Fcount <Ftable, it is stated that Ha is rejected and Ho is accepted. Based on the results of the above study, it was concluded that there was no influence between extroverted and introverted personality types on students' speaking skills.